A organização do trabalho como fonte geradora de prazer e sofrimento em enfermeiros que atuam em unidades de terapia intensiva: uma análise à luz da psicodinâmica do trabalho - Araújo, Angélica Barros (2023)
Introduction: The role of nurses in the Intensive Care Unit is fundamental for the care and recovery of critical or terminal patients, configured by the involvement of specific challenges and demands that can affect both their mental health and their professional satisfaction. To better understand this dynamic and its effects on the worker's psychic balance, Psychodynamics of Work is sought as a field of study to investigate the psychic and social processes that are present in the organization of work, considering aspects such as pleasure, suffering and defensive strategies. Objective: To identify aspects inherent to the organization of work perceived by nurses who work in Intensive Care Units. Method: Qualitative and descriptive research, carried out in a university hospital, located in the state of Paraíba. The sample consisted of 19 nurses from the adult, neonatal and pediatric intensive care sectors. The collection took place through a semi-structured form with objective and subjective questions relevant to the theme, with data analysis through Content Analysis. There was appreciation by the institution's Ethics and Research Committee, under opinion No. 5.659.108. Results: Five analytical categories emerged, including nurses' work process, interpersonal relationships in the work environment, pleasure and suffering in nurses' work, and use of individual and collective defensive strategies. From these five categories, twenty thematic subcategories unfold. Conclusion: The results obtained allowed us to reflect on the perceptions about the work of nurses in the intensive care unit, addressing their suffering, pleasure and defensive strategies. These reflections contributed to broaden the knowledge of the Psychodynamics of Work in this specific context, highlighting the psychic and social processes that involve the meanings of work for professionals.